Biochemical Test and Antimicrobial Potentials of Bandotan (Ageratum conyzoides) Leaves against Pathogenic bacteria in the Water - Riang Adeko; Hidayat, Habibi; Andriana Marwanto; Sri Mulyati; Wiwit Aditama (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2024)
Water cleaning technology using coagulation has already been carried out use a plants in the coagulation process has never been done before, especially using plants that have potential to be a source of natural coagulants is Bandotan (Ageratum conyzoides). Plants that have the potential to be a source of natural coagulants are plants that contain a lot of protein. Each type of protein has an isoelectric point at a different pH like isoelectric point, the protein will have a neutral charge. . The calculation results of the number of colonies in samples were B1, B2, and B3 with dilutions of 266. 105, 9. 107 and 104. 109 CFU/mL. The results of Gram staining identification showed that the B1, B2 and B3 isolates had the shape are basil, basil and coccus (round) with Gram positive. The bacteria thrive in different habitats, so bacteria from the sample have been very cloudy to pH of 6.0 and 8.0 because neutralophiles properties. From the B3 isolate sample have high clear zone for Gram positive (S. aureus) of 13 mm more than Gram negative ( E. coli) of 11 mm. So that, the bandotan is able to inhibit the growth of pathogenic bacteria in the water